CARDIAC RISK ASSESSMENT IN THE ELECTIVE ABDOMINAL AORTIC SURGERY - Djokić, Ivana; Jović, Miomir (Medicinski podmladak, 2023)
When indicated, patients with abdominal aortic aneurysm and aortoiliac occlusive disease are referred for elective abdominal aortic surgery. Abdominal aortic aneurysm repair and aortoiliac reconstruction are associated with a high risk for the development of cardiovascular morbidity and mortality. Cardiac risk assessment in abdominal aortic surgery includes evaluation of the likelihood of adverse cardiac events during surgery or in the postoperative period. Overall cardiac risk is assessed individually for the patient, taking into account the patient's general condition, cardiac function, patient functional capacity, comorbidity status, and vascular surgery risk. Cardiac morbidity and mortality are several times higher in emergency procedures than in elective abdominal aortic procedures, in surgical procedures compared with endovascular procedures, especially in patients with suprarenal clamping of the aorta. Patients with ischemic heart disease and heart failure are at high risk for adverse cardiac events. Pathophysiologic mechanisms activated intraoperatively by aortic clamping and unclamping, hemodynamic fluctuations, blood loss, coagulopathy, and ischemia-reperfusion injury influence the potential development of perioperative infarction, heart failure, and cardiac arrest in high-risk patients. Assessment of perioperative cardiac function and cardiac risk using leading recommendations and scoring systems before surgery may change the approach to management of high-risk patients with multiple comorbidities and significantly reduce the incidence of perioperative morbidity and mortality.
Keywords: cardiac risk, abdominal aortic aneurysm, aortoiliac occlusive disease